Partial structural functions of binary liquids estimated from anomalous X-ray scattering measurements - Waseda, Y (Journal of synchrotron radiation, 1998)
A new apparatus has been built for structural studies of high-temperature liquids using the anomalous X-ray scattering (AXS) method with synchrotron radiation. AXS measurements were made in the asymmetrical reflection mode for a free liquid surface by changing the beam direction using an additional mirror system. The usefulness and capabilities of this new equipment were confirmed by obtaining the individual partial structural functions of liquid Bi(30)Ga(70) alloy